(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2024)
In this study, the activated carbon that was obtained from date seeds, after heating at 500 ºC, was used to remove methyl red dye from its aqueous solutions. Different parameters were applied including (the effect of dose, the effect of adsorption time, and the effect of pH value). The extent of dye removal increased with increasing adsorption time. An acidic pH is optimal for enhancing dye adsorption. The Langmuir isotherm was applied to the data obtained, and its constants were calculated at the optimum conditions. According to Langmuir isotherm, the monolayer saturation capacity (q m ) is 0.9 mg/g. The study concluded that date seeds activated carbon (DSAC) has demonstrated effective adsorption results in removing methyl red and suggests its potential for use in other adsorption studies.